ANALISIS LITERASI LINGKUNGAN PADA SISWA SMA NEGERI 5 SAWANGAN KOTA DEPOK JAWA BARAT - Setianti, Ning (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
The decline in the quality of environmental and natural conditions emphasizes the importance of humans having a healthy ecosystem. This must be done by changing thought patterns and behavior in every production and consumption process on a larger scale through environmental literacy education. The research problem regarding the environmental literacy of students at SMA Negeri 5 Depok is analyzed through four parts, namely ecological knowledge, cognitive skills, attitudes and behavior towards the environment. The aim of the research is to determine and analyze four indicators of environmental literacy, namely ecological knowledge, cognitive skills, attitudes and behavior towards the environment of students. The research method uses a qualitative descriptive approach. The research was conducted at SMA Negeri 5 Sawangan, Depok City, West Java Province with the research sample being class X Science 2 students, totaling 40 students. The research results showed that four indicators of environmental literacy, namely ecological knowledge, cognitive skills, attitudes and behavior towards the environment of students, increased from cycle I to cycle II. The research conclusion is that environmental literacy can increase students' awareness of current environmental conditions, if each subject is presented by the teacher in class, so it is hoped that it can have an impact on students' environmental literacy levels.